«Challenge to Reason»: Fridrich Nietzshe and Lev Shestov - Rumyantseva, Tatsiana G. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article is devoted to outstanding Russian philosopher and writer, a representative of Russian religious philosophical revival of the early ХХ century – Lev Shestov, 150-year anniversary of whose birth was widely celebrated in 2016 worldwide. It seems that Shestov’s anniversary will be a good occasion to draw attention to this remarkable thinker, whose works are well known not only in Russia and the countries of the former USSR, but also abroad, where he spent most of his life. Based on the fact that the main theme of all the Shestov’s works was sharp criticism of rationalism as the culprit, in his view, of all human suffering, as well as the fact that a decisive role in the formation of his philosophical views, along with the works of W. Shakespeare, L. Tolstoy and F. Dostoevsky, played ideas of F. Nietzshe, the author attempted to identify common ground in the views of both thinkers who challenged the reason. It is shown that, existentially experiencing the tragedy of human existence, the Russian philosopher, like his idol Nietzsche, sharply criticized the science, as the embodiment of reason, proclaiming his famous appeal to the so-called «Groundless», as the exact opposite to the creating system settings of philosophical reason.